Ministry of Land Responsibility For Mortgage Rights on Certificates Burdened by Land And Building Duty - Amaliah, Ana; Safa’at, Rachmat; Istislam, Istislam (The Islamic Education and Multiculturalism Foundation, 2025)
This study discusses the responsibility of the Ministry of Land Affairs in issuing Mortgage Rights for land certificates that are still subject to Land and Building Acquisition Fees. This study uses an empirical method. Data were obtained through analysis and primary data from interviews with the Land Office, creditors, and local governments, secondary data from laws and regulations, and tertiary data from literature and related legal documents. The results of the study indicate that verification of Land and Building Acquisition Fee payments before the issuance of Mortgage Right certificates is still not optimal due to the coordination agreement between the Land Office and local governments. In addition, a weak data integration system and low public awareness of the obligation to pay Land and Building Acquisition Fees also contribute to this problem. As a result, there is a risk for creditors in executing collateral and obstacles for debtors in the process of transferring land rights.